2006
DOI: 10.1093/ps/85.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Slower-Growing Broiler Genotypes Grown with and Without Outdoor Access: Sensory Attributes

Abstract: Consumer interest in organic and natural poultry production is growing. An experiment was conducted to assess the impact of genotype and outdoor access on sensory attributes of broiler meat. One slow-growing genotype (S), 2 medium-growing genotypes (M1 and M2), and a commercial fast-growing genotype (F) were raised (straight-run) for 81, 67, or 53 d, respectively. The placement dates were staggered to achieve a similar final BW, and each genotype was processed on the same day. Each genotype was assigned to 3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 8 publications
4
57
1
3
Order By: Relevance
“…Even though meat from slow-growing genotypes is reputed to have superior texture (Fanatico et al, 2006), some studies have found the tenderness of broiler meat to decrease with age (Berri, 2000). In the present study we found that meat was less tender and juicy, and harder in the traditional broiler hybrid JA757 when it was slaughtered at 110 d of age.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Even though meat from slow-growing genotypes is reputed to have superior texture (Fanatico et al, 2006), some studies have found the tenderness of broiler meat to decrease with age (Berri, 2000). In the present study we found that meat was less tender and juicy, and harder in the traditional broiler hybrid JA757 when it was slaughtered at 110 d of age.…”
Section: Discussioncontrasting
confidence: 41%
“…How the consumers will perceive these differences in sensory quality is presumably related to the geographical and cultural origins of the consumer (Berri, 2000). In addition, other quality dimensions may influence consumer perception (Fanatico et al, 2006) and thus the extent to which a premium price is obtainable.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of consumers' requests, the alternative systems, for example, free-range, Label Rouge and organic production systems, have been developed for broiler meat production (Sales 2014). Basic conditions of these systems are prohibition of antibiotics for growth and synthetic substances, and providing of access to outdoor called as pasture (Fanatico et al 2006). These production systems have to meet minimum husbandry standards such as: a slow-growing bird, foodstuffs low in fats and high in cereals (at least 65-70%), low stocking rates (maximum of 11 birds/m 2 ) and a pasture area of 2 m 2 per bird, minimum slaughter age 81 days (Saveur 1997;Fanatico 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing interest in rearing chicken under semi-intensive and extensive systems (Fanatico et al, 2006;Pavlovski et al, 2009;Bancos, 2010), as well as to the possibility of decreasing production costs and using available on the market commercial line chickens, it is justifiable to undertake research in this area.…”
Section: Introductionmentioning
confidence: 99%